MENINGKATKAN SISTEM KEARSIPAN ELEKTRONIK SEKOLAH DENGAN BUDAYA MANUNGGU DURIAN - Muzwarto Muzwarto (Jurnal Economic Edu, 2021)
The background of this paper is an important document records management schools that are not organized and are not secured properly so that when the data is needed is hard to find . The cause is still conventional storage system making it less effective and less safe . Tupoksi, appropriate school superintendent, the author of innovating is to build an electronic records management system of schools using IT. The approach used is culture manunggu durian. In this approach , there are several steps that must be implemented . In addition , there are also the values that are beneficial in fostering a school management that the value of tenacity / kegihan, patience and discipline. Keywords: Managerial, mananjemen, manunggu durian culture and manunggu durian values